The Analysis of Coherence in Writing Personal Recount Essay - Darma, Suci Dwina (Jurnal Pendidikan Vokasi Raflesia, 2025)
This research aimed to analyze the coherence in writing personal recount essay that had been written by students of Stikes Al Fatah Bengkulu for second semester. This research also to know the coherence in students writing for personal recount essay which was focused on firstly: content of essay that consisted of introduction, content of essay and closing of paragraph. Secondly, focused on language of structure or grammatical and writing organization in essay. The population of this research was 30 students of second semester of Stikes Al Fatah Bengkulu by using purposive sampling method. The result of this research showed that there are 2 essays got 6.66% in very good category, 16 essays got 53.33% in good category, 10 essays got 33.33% in barely acceptable essay, 2 essays got 6.66% in poor essay. At least, there were 18 essays showed the coherence in writing were better than 12 other essays.